The Use of Adjunctive Steroids in Central Nervous Infections - Gundamraj, Shalini; Hasbun, Rodrigo (Frontiers in Cellular and Infection Microbiology, 2020)
Central nervous system (CNS) infections continue to be associated with significant neurological morbidity and mortality despite various existing therapies. Adjunctive steroid therapy has been employed clinically to reduce inflammation in the treatment of CNS infections across various causative pathogens. Steroid therapy can potentially improve clinical outcomes including reducing mortality rates, provide no significant benefit, or cause worsened outcomes, based on the causative agent of infection. The data on benefits or harms of adjunctive steroid therapy is not consistent in outcome or density through CNS infections, and varies based on the disease diagnosis and pathogen. We summarize the existing literature on the effects of adjunctive steroid therapy on outcome for a number of CNS infections, including bacterial meningitis, herpes simplex virus, West Nile virus, tuberculosis meningitis, cryptococcal meningitis, Angiostrongylus cantonensis, neurocysticercosis, autoimmune encephalitis, toxoplasmosis, and bacterial brain abscess. We describe that while steroid therapy is beneficial and supported in pathogens such as pneumococcal meningitis and tuberculosis, for other diseases, like Listeria monocytogenes and Cryptococcus neoformans they are associated with worse outcomes. We highlight areas of consistent and proven findings and those which need more evidence for supported beneficial clinical use of adjunctive steroid therapy.